2020
DOI: 10.1155/2020/6108362
|View full text |Cite
|
Sign up to set email alerts
|

The Role of IL-33 in Experimental Heart Transplantation

Abstract: Interleukin-33 (IL-33) is a member of the IL-1 family of proteins that are produced by a variety of cell types in multiple tissues. Under conditions of cell injury or death, IL-33 is passively released from the nucleus and acts as an "alarmin" upon binding to its specific receptor ST2, which leads to proinflammatory or anti-inflammatory effects depending on the pathological environment. To date, numerous studies have investigated the roles of IL-33 in human and murine models of diseases of the nervous system, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 99 publications
0
3
0
Order By: Relevance
“…Among patients receiving kidney transplantation, serum levels of IL-33 were higher in chronic allograft dysfunction patients compared to patients with stable graft function [ 257 ]. The research on cardiac IR and IR-induced myocardial injury found that IL-33 may have beneficial effects by suppressing inflammatory cytokines’ expression and myocardial apoptosis, and increasing production of Th2 type cytokines and an upset in the balance of Th1/Th2 responses during heart transplantation [ 263 , 264 ]. Donor mouse cardiac allografts deficient in IL-33 exhibited dramatically accelerated vascular occlusion and subsequent fibrosis, which was accompanied by local proinflammatory iNOS + macrophage augmentation [ 265 ].…”
Section: Il-33 and Immune-related Diseasesmentioning
confidence: 99%
“…Among patients receiving kidney transplantation, serum levels of IL-33 were higher in chronic allograft dysfunction patients compared to patients with stable graft function [ 257 ]. The research on cardiac IR and IR-induced myocardial injury found that IL-33 may have beneficial effects by suppressing inflammatory cytokines’ expression and myocardial apoptosis, and increasing production of Th2 type cytokines and an upset in the balance of Th1/Th2 responses during heart transplantation [ 263 , 264 ]. Donor mouse cardiac allografts deficient in IL-33 exhibited dramatically accelerated vascular occlusion and subsequent fibrosis, which was accompanied by local proinflammatory iNOS + macrophage augmentation [ 265 ].…”
Section: Il-33 and Immune-related Diseasesmentioning
confidence: 99%
“…However, there are significant differences between levels of mast cells in mice and humans, which may reduce the translatability of these findings. Even so, IL-33 is thought to have a protective role in reducing heart allograft and xenograft rejection [38]. This protective role was demonstrated with reduced immune response-related damages and suggested that IL-33 could be developed as a therapeutic approach to transplant rejection [38].…”
Section: Effects Of Il-33 On the Cardiovascular And Pulmonary Systemsmentioning
confidence: 99%
“…Even so, IL-33 is thought to have a protective role in reducing heart allograft and xenograft rejection [38]. This protective role was demonstrated with reduced immune response-related damages and suggested that IL-33 could be developed as a therapeutic approach to transplant rejection [38].…”
Section: Effects Of Il-33 On the Cardiovascular And Pulmonary Systemsmentioning
confidence: 99%